Survival predictor for penetrating cardiac injury; a 10-year consecutive cohort from a scandinavian trauma center - Kaljusto, Mari-Liis (Scand J Trauma Resusc Emerg Med, 2015)
BACKGROUND: Penetrating cardiac injuries in Europe have been poorly studied. We present a 10-year outcome for patients with penetrating heart injuries at Oslo University Hospital. METHODS: Data from 01.01.2001 until 31.12.2010 was collected from the Oslo University Hospital Trauma Registry and from the patients’ records. RESULTS: Thirty-one patients were admitted with a penetrating cardiac injury. Fourteen patients survived (45 %). Four out of 8 patients (50 %) with gunshot wounds survived compared to 10 out of 23 (44 %) with stab wounds. Median (quartiles) for the following values were: Injury Severity Score 25 (21–35), Revised Trauma Score 0 (0–6,9), Probability of Survival 0,015 (0,004–0,956), Glasgow Coma Scale 3 (3–13). Thirteen patients had signs of life on admission and survived. Eighteen patients were admitted without signs of life and received emergency department thoracotomy. Eight of these had no signs of life at the scene of injury and did not survive. Out of the remaining 10 patients, one survived. CONCLUSIONS: The outcome of patients with penetrating cardiac injury reaching the emergency department with signs of life was excellent. Hemodynamic instability indicates immediate surgery. Stable patients with penetrating thoracic trauma and possible cardiac injury detected by imaging should be considered for conservative treatment.